Desert Microbes for Boosting Sustainable Agriculture in Extreme Environments - Alsharif, Wiam; Saad, Maged M.; Hirt, Heribert (Frontiers in Microbiology, 2020)
A large portion of the earth’s surface consists of arid and semi-arid land. Life in these regions is profoundly challenged by water limitation, high levels of solar radiation and temperature fluctuations, along with high salinity and low nutrients of the soil. These harsh environmental conditions impose serious threats to plant growth. Low yield and poor quality of crops in these areas impose threats to global food security and sustainability. In recent years, not only plants that grow in such extreme environments but also their naturally associated beneficial microorganisms have attracted increased interest. Desert plants display a perfect niche for isolating novel microbial strains that are well adapted to extreme environments and offer an unexploited reservoir for bio-fertilizers and bio-control agents. Their properties can be used to improve soil fertility, increase plant tolerance and crop productivity as well as benefit human health thereby providing food for a growing human population in an environment-friendly manner. In this review, we will describe the efforts to explore the microbial diversity of arid and semi-arid regions highlighting the latest discoveries and applications of microbes from deserts around the world.